2014
DOI: 10.4049/jimmunol.1401192
|View full text |Cite
|
Sign up to set email alerts
|

IL-1R1 Signaling Regulates CXCL12-Mediated T Cell Localization and Fate within the Central Nervous System during West Nile Virus Encephalitis

Abstract: Immune cell entry into the virally infected central nervous system (CNS) is vital for promoting viral clearance yet may contribute to neuropathology if not rigorously regulated. We previously showed that signaling through the interleukin 1 receptor (IL-1R1) is critical for effector T cell reactivation and virologic control within the CNS during murine West Nile virus (WNV) encephalitis. WNV-infected IL-1R1−/− mice also display increased parenchymal penetration of CD8+ T cells despite lack of CD4-mediated full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 84 publications
(123 reference statements)
3
55
0
Order By: Relevance
“…As previous studies have suggested that early WNV neuroinvasion can be caused by defects in BBB function (4,27,28), we determined whether BBB permeability was altered differentially in the cerebellum and cerebral cortex of Cre -littermate controls. Analysis of extravasation of sodium fluorescein (376 Da) on various days following s.c. infection showed biphasic kinetics, as observed in our previous studies (4,21), with an enhancement of BBB permeability on day 4 after infection, decreased permeability on days 5 and 6, and a reopening of the BBB on day 8 ( Figure 1H). While loss of IFNAR signaling in astrocytes led to enhancement of BBB permeability in both cerebral cortical and cerebellar tissues after infection, the kinetics of these effects differed between regions.…”
Section: Cerebellum (961%) Analysis Of Ifnar Expression On Map2supporting
confidence: 84%
See 3 more Smart Citations
“…As previous studies have suggested that early WNV neuroinvasion can be caused by defects in BBB function (4,27,28), we determined whether BBB permeability was altered differentially in the cerebellum and cerebral cortex of Cre -littermate controls. Analysis of extravasation of sodium fluorescein (376 Da) on various days following s.c. infection showed biphasic kinetics, as observed in our previous studies (4,21), with an enhancement of BBB permeability on day 4 after infection, decreased permeability on days 5 and 6, and a reopening of the BBB on day 8 ( Figure 1H). While loss of IFNAR signaling in astrocytes led to enhancement of BBB permeability in both cerebral cortical and cerebellar tissues after infection, the kinetics of these effects differed between regions.…”
Section: Cerebellum (961%) Analysis Of Ifnar Expression On Map2supporting
confidence: 84%
“…This enhanced BBB permeability is associated with earlier detection of WNV in hindbrain regions of the CNS, suggesting that astrocyte IFNAR signaling prevents or delays infection at this site. Altered expression of cytokines such as IL-1β also probably influences other functions of the BBB, including local antigen presentation (21,45) and perivascular capture of infiltrating leukocytes (9,46), as reflected by the broad parenchymal localization of CD3 + lymphocytes in our study. Regional differences in astrocyte signaling may also differentially impact regional differences in other neurovascular cell types, including endothelial cells.…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…Elimination of virus-infected cells in the CNS requires a CD8 T-cell response [233][234][235][236]. In response to WNVand JEV infections, neurons release CXCL10, which is required for recruitment of CD8 T cells into the brain via the C-X-C chemokine receptor (CXCR)3 [151,170].…”
Section: Viral Clearance From the Cnsmentioning
confidence: 99%